Las obligaciones tributarias y el nivel de cumplimiento en la empresa oriental Industria alimenticia O.I.A. Cia. Ltda., cantón Quevedo, - Suárez Suárez, Johana Carolina (2015)
This research work on the theme: TAX LIABILITIES AND LEVEL OF COMPLIANCE IN THE COMPANY ORIENTAL FOOD INDUSTRY OIA CIA. LTDA., CANTON Quevedo, YEAR 2012 allowed us to learn, analyze and develop a Tax Audit through it can detect the procedure yielded information on the degree of compliance with the feudatory obligations and the effective tax burden are bearing the companies, it is also an effective way of monitoring the same feedback that helps managing economic entities. The instrumentalization of control systems are given through the audits that apply in companies within a given period to meet their constraints, problems, weaknesses and incidence and improve tax administration possessing taxpayers regarding the taxes generated and application of rules, laws, tax regulations and / or policies, control and payment of taxes. The thesis is structured into chapters which enabled them to obtain the following results of this research, checking Agribusiness 0% presented absence of internal audit department in the company; causing a 100% risk their feudatarios controls them should be monitored as provided by the rules and policies, compliance with laws 80% of correct application of the tax law and 20% was found remaining is due to the instability of delivering the withholding outside the specified time, proceeding to compare and check the items reported on Form 101 to the statement of income tax to the Financial Statements of the company was detected 100% reliability calculations reconciled in this procedure thus effecting the absolute and relative change to meet the increase and decrease of each account; and the indicator applied on internal and external risks proceeded to review information from the sales of the Oriental getting 2% of invoices canceled only by not using them.